Would Marjolin see it coming? Two unusual cases of squamous cell carcinoma. (2018) - Ben Naftali, Yeela; Duek, Ori Samuel; Kalus, Ram; Berns, Marc; Zohar, Yaniv; Ullmann, Yehuda
Highlights: Aggressive behavior of SCC in young patients is uncommon. Diagnosed a year after first signs of the lesion; One previously diagnosed as an abscess, the other as necrotizing fasciitis. These delayed diagnoses might be a contributing factor to the tumor aggressiveness. Hence, a tissue diagnosis is necessary to rule out malignancy in chronic lesions, taking Marjolin's ulcer into account. Abstract: Introduction: Cutaneous squamous cell carcinoma (SCC) is a common skin cancer, second in incidence only to basal cell carcinoma (BCC). The incidence of SCC increases significantly with age; thus, it is rarely diagnosed in young patients. In this paper, we present two cases of young patients who presented clinically with purulent lesions that were later diagnosed as large primary SCCs. Materials and methods: A review of the medical records of two patients who were admitted to the department of plastic surgery with a final clinical diagnosis of cutaneous SCC was conducted. Information of the review included history, physical examination, laboratory tests, imaging studies and histology. A literature review was also conducted and discussed. Results: Two female patients under the age of 45 presented with large, purulent lesions that were initially clinically suggestive of an infectious etiology. The lesions were surgically treated by incision and drainage without sending tissue samples to pathology. Biopsies of the lesions were performed to obtain a tissue diagnosis due to recurrence approximately one year after the initial treatment. Histological evaluation revealed well differentiated squamous cell carcinomas. Surgical intervention with wide excision with adjuvant chemotherapy was recommended based on biopsy and CT scan results. Discussion: Aggressive behavior of SCC in young patients is uncommon. The patients in this report were diagnosed only one year after the first sign of the lesion. One patient was first diagnosed with an abscess, and the other with necrotizing fasciitis. The delayed diagnosis of SCC in these two patients is a potential contributing factor to the aggressiveness of the tumors. Therefore, it is imperative to perform skin biopsies of chronic or persistent purulent lesions to rule out malignancies including Marjolin's ulcer. Conclusion: Aggressive SCC should be suspected in cases of persistent and relapsing purulent lesions in all patients.